LOS PROCESOS DIDÁCTICOS PARA MEJORAR LA COMPRENSIÓN LECTORA EN LOS ESTUDIANTES DEL QUINTO GRADO DE SECUNDARIA DE LA I.E. SAN AGUSTÍN-LEYMEBAMBA - 2023 - Castro Escobedo, Elena Margarita (2023)
The present research called “Didactic processes to improve reading comprehension in fifth grade secondary school students of the I.E. San Agustín-Leymebamba–2023”, had the main objective of demonstrating the improvement of reading comprehension through the application of didactic processes. The type of research was applied with a quantitative approach, with a pre-experimental design based on pre-test-post-test with a single group. The population was made up of 43 students enrolled in the two sections of the fifth grade. The sample consisted of 21 schoolchildren, the instrument used was an objective test developed with a rubric with an assessment scale by achievement levels. In the results of the pre-test, 76% were located at the Start achievement level, 10% were located at the process level and 14% were at the achieved level, while in the exit test, 24% achieved the process level, 57% achieved the level achieved and 19% are positioned as Outstanding. It is concluded that the correct application of didactic processes during reading significantly improves reading comprehension.